Enhancing paper strength through blending approach: incorporating oil palm frond fiber into recycled pulp - Lee, Man Djun; Lee, Pui San; Hazim Sharudin,; Azmi Roslan,; Miqdad Khairulmaini,; Ahmad Faidzal Khodori, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Recycled fibers often demonstrate diminished conformability and inter-fiber bonding capabilities in comparison to virgin fibers due to hornification. However, the untapped potential of recycled pulp can be restored through various techniques, such as mechanical beating, additive utilization, physical fractionation, and blending. This research focuses specifically on the blending method, which utilizes oil palm frond fibers to augment the strength of paper produced from recycled pulp. Despite the extensive cultivation of oil palm trees in Malaysia, the utilization of oil palm fiber remains limited and is frequently considered waste material. Two distinct chemical pulping methods, namely sodium hydroxide and sodium sulfite, were employed to generate pulp from oil palm frond fibers, incorporating anthraquinone as an additive to enhance pulping efficiency. Three different weight percentages of fiber loading (25%, 45%, or 65%) were utilized, with the remaining content supplemented with newspaper pulp. The resultant paper was assessed for tensile strength, modulus of elasticity, and its morphology was examined using scanning electron microscopy. The findings indicate that the sulphite-soda anthraquinone treatment resulted in superior pulp for paper production, and a weight percentage of 45% fiber loading exhibited the highest tensile strength, thus yielding the highest quality paper. Overall, this study underscores the potential of integrating oil palm frond fibers into the pulp and papermaking process, thereby contributing to both economic growth and environmental sustainability.